Batasan Usia Perkawinan dalam Perspektif Ulama Klasik dan ‎Kontemporer - Moh Hatta (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2016)
Abstract: Determination of the age limit for marriage is very important, because a marriage in addition to biological maturity also requires psychological. Marriage age restrictions are not discussed in the books of fiqh. Even the books of fiqh allow mating between males and females are still small. However, the absence of proof that explicitly limits the age of marriage is not the end of the establishment of a law. This paper wants to examine how the opinions of the scholars of the age limit of marriage, especially in classical and contemporary scholars, which in this case is focused on the opinion of Ibn Kathir (as classical scholars) and Rashid Rida (as contemporary scholars). At the end of the article concluded that bulugh al-nikah according to Ibn Kathir (classical scholars) means old enough or smart, while according to Rashid Rida (contemporary scholars) means the arrival of a person to age for marriage, namely to dream. The difference is because the interpretation of Ibn Kathir more focused on the physical aspect of the outward and simultaneously have mukallaf, while Rashid Rida focuses on the mental side, which is seen in the attitudes and behavior.Â Abstrak: Penentuan batas umur untuk perkawinan sangatlah penting sekali, dikarenakan suatu perkawinan disamping menghendaki kematangan biologis juga psikologis. Batasan usia perkawinan tidak dibicarakan dalam kitab-kitab fiqih. Bahkan kitab kitab fiqh memperbolehkan kawin antara laki-laki dan perempuan yang masih kecil. Namun, ketiadaan dalil yang secara eksplisit mengungkapkan batas usia nikah bukanlah akhir dari penetapan suatu hukum. Tulisan ini ingin mengkaji bagaimanakah pendapat para ulama tentang batasan usia pernikahan, terutama menurut ulama klasik dan kontemporer, yang dalam hal ini difokuskan pada pendapat Ibn Kathir (sebagai ulama klasik) dan Rashid Ridha (sebagai ulama kontemporer). Di akhir tulisan disimpulkan bahwa bulugh al-nikah menurut Ibn Kathir (ulama klasik) berarti cukup umur atau cerdas, sedangkan menurut Rashid Ridha (ulama kontemporer) berarti sampainya seseorang kepada umur untuk menikah, yakni sampai bermimpi. Perbedaan penafsiran ini dikarenakan Ibn Kathir lebih menitik beratkan pada segi fisik lahiriyah dan sekaligus telah mukallaf, sedangkan Rasyid Ridha menitik beratkan pada segi mental, yakni dilihat pada sikap dan tingkah laku seseorang.